Mengkaji Perkembangan Partisipasi Warga Negara Dalam Tata Kelola Pemerintahan Yang Baik - Karina Asiyah Dwitasari (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
The discussion of citizen participation in governance is not an entirely new one. Citizen participation is an important aspect of good governance, using its role as an integral part of human rights. Participation is able to encourage citizens to participate in giving consideration, supervision, and evaluation of the implementation of government. So that maladministration efforts can be prevented to a minimum. In this case, citizen involvement in government is the core of democratic life and the realization of the Sustainable Development Goals (SDGs). This research uses a qualitative approach with a literature review research method. This article explains the development of the meaning, implementation, and challenges faced by the development of citizen participation. Efforts that can be used to overcome obstacles to citizen participation are also discussed. This study shows that the development of participation is expected to increase citizen involvement to the maximum. In addition, this article also focuses on the need for meaningful citizen participation in realizing good governance.